Wellness Center with Healing Environment Approach in Tangerang City - Ardimas Bima Pamungkas; Wiwit Setyowati; Teguh Prihanto; Ari Rahadini (Universitas Negeri Semarang, 2024)
After the COVID-19 pandemic, global focus on health has increased, including mental health issues. However, many people in Indonesia still consider mental health to be a taboo subject. In reality, mental health has a significant impact on community life. Poor mental health, such as stress, anxiety, and depression, can negatively affect physical well-being and reduce the quality of life, particularly in large cities like Tangerang. Tangerang's numerous industrial factories contribute to air pollution, the lack of green spaces, and significant social pressures, all of which increase stress among its residents and can lead to mental health issues that may result in harmful actions toward themselves or others. In 2018, TangerangNews reported 15 suicide incidents in Tangerang City, Tangerang Regency, and South Tangerang, with causes ranging from economic factors to depression. According to Pasla (2023), several methods can prevent the negative impacts of mental health issues, including maintaining and improving mental well-being through actions that balance physical and spiritual conditions. In response to these challenges, the planning and design of a Wellness Center could be an inspiring solution with the potential to positively impact the community in Tangerang. Integrated with the Healing Environment approach, which creates a more healing and restorative building environment, this facility aims to enhance community wellness in a positive, targeted, and effective manner, reducing stress levels and preventing depression to improve the quality of life in Tangerang.